Operational reliability assessment of power systems based on bus voltage. Issue 5 (1st April 2015) - Qin, Wenping; Song, Jiancheng; Han, Xiaoqing; Wang, Peng
Abstract : Bus voltage is a direct reliability indicator of a transmission network because it is related to system reactive and active power balance especially during a contingency state. This study proposes a technique to evaluate network operational reliability based on bus voltage. Two new voltage related bus reliability indices are proposed to represent bus reliability. Network reliability levels under various operating conditions and contingency states are evaluated and presented by probabilities of system voltage being in normal, under‐voltage, critical and collapse zones. The probabilistic voltage margin to the collapse point for each bus is evaluated to provide information for system operator regarding the risk under system random failures and load uncertainty. The IEEE 30‐bus system and a practical 220 kV Taiyuan power system in Shanxi Province of China have been analysed to illustrate the proposed techniques.